The Differences on Triglyceride Levels was Centrifuged Samples after Freezing for 30 Minutes and 2 Hours - Wardani, Hesti Diah Ayu Kusuma; Saktiningsih, Hari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Laboratory testing is part of health services that support efforts to improve health, prevent and diagnose disease. This service includes hematology, clinical chemistry, clinical immunology, clinical microbiology, and clinical parasitology. Differences in triglyceride levels are caused by hydrolysis and oxidation processes due to storage at room temperature. This study aims to compare triglyceride levels in centrifuged samples after freezing for 30 minutes and 2 hours. This study used an experimental research design. This research was conducted in the National STIKES laboratory. The samples used were 21 samples from class 2A1 of the DIII Medical Laboratory Technology Study Program of the National College of Health Sciences obtained by the quota sampling technique. The results of the normality test of triglyceride level examination data on samples frozen 30 minutes 0.057 and frozen 2 hours 0.196. These results are normally distributed, because the sig value> 0.05. Then continued the paired T test obtained the result of 0.001. From the results obtained, it can be concluded that there are differences in centrifuge samples after being frozen for 30 minutes and 2 hours.